The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1667/rr1625.1
|View full text |Cite
|
Sign up to set email alerts
|

UVB Radiation Induces Persistent Activation of Ribosome and Oxidative Phosphorylation Pathways

Abstract: Ultraviolet B (UVB) radiation has strong biological effects and modulates the expression of many genes. The major biological pathways affected by UVB radiation remain controversial. In this work, we used a loop-design microarray approach and applied rigorous statistical analyses to identify differentially regulated genes at 4, 8, 16 or 24 h after UVB irradiation. The most prominent biological categories in lists of differentially regulated gene sets were extracted by functional enrichment analysis. With this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Table S1 shows the number of DEGs and SGs in each exposed group, and no SG was observed between the internal control samples. The SGs of the positive control revealed genes involved in oxidative phosphorylation and ribosome pathways, which are in good agreement with prior studies in which other human cell types were used as experimental models [22], [29][32]. The results of the internal and positive controls indicated that the loop-designed microarray approach is a reliable system for screening the transcriptional profiles of HaCaT cells exposed to ELF-EMFs.…”
Section: Resultssupporting
confidence: 88%
“…Table S1 shows the number of DEGs and SGs in each exposed group, and no SG was observed between the internal control samples. The SGs of the positive control revealed genes involved in oxidative phosphorylation and ribosome pathways, which are in good agreement with prior studies in which other human cell types were used as experimental models [22], [29][32]. The results of the internal and positive controls indicated that the loop-designed microarray approach is a reliable system for screening the transcriptional profiles of HaCaT cells exposed to ELF-EMFs.…”
Section: Resultssupporting
confidence: 88%
“…As discussed in our previous study, after UVB irradiation, the up-regulation of genes related to translation and ribosomal proteins in human fibroblasts suggested the need to renew UVB-damaged ribosomal proteins [18]. This corresponds to the result by the Casati and Walbot study, which showed that UVB irradiation induced direct ribosomal damage by crosslinking ribosomal proteins to RNA [41].…”
Section: Discussionsupporting
confidence: 80%
“…These 13 genes are related to chromosome condensation, DNA repair, cell cycle arrest, and apoptosis (Figure 3; related literatures are listed in Text S1). Previously we have validated our microarray system by RT-PCR with randomly selected genes, and the results were generally good (with R 2 ranged from 0.86 to 0.94) [18], [25][26]. To verify the significant gene expression patterns in this study, we further performed RT-PCR analysis for certain UVB-regulated genes, including the transcriptional targets of p53 ( GADD45A and CDKN1A ), one antioxidant gene ( GPX1 ), and three of the most discrepant genes ( MEN1 , NCAPH , and IL8 ).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations